CRISPR-Cas Systems: From Gene Scissors to Programmable Biosensors. - Zhang, Y; Wu, Y.; Wu, Y.; Chang, Y.; Liu, M.
The increasing needs for developing biosensors for various applications in infectious disease diagnosis, environmental monitoring, and food safety put forth challenges on sensor performances such as sensitivity, selectivity, assay time, and operation cost. The CRISPR-Cas systems, regarded as molecular scissors, present an extremely high accuracy toward cleaving the targeted DNA and RNA. The presence of a target triggers the activation of CRISPR-Cas system to cleave the specific nucleic acid sequence and generate a signal. Recent studies have demonstrated the establishment of various facile and versatile CRISPR-Cas-based biosensing platforms. In this review, we will briefly introduce the general characteristics and mechanisms of the class II CRISPR-Cas systems, and highlight the biosensing strategies for a wide variety nucleic acid and non-nucleic acid analytes
Keywords: BIOSENSING; CRISPR-CAS; NUCLEIC ACID DETECTION; NON-NUCLEIC ACID DETECTION